Sensitive Stretchable and Pressable Mechanochromic Photonic Crystals for Dynamic Displays and Visual Sensing - Boru Wei; Yang Hu; Dongpeng Yang; Shaoming Huang (Advanced Sensor Research, 2023)
Abstract Mechanochromic photonic crystals (MPCs) have shown wide applications in visual sensing, displays, anti‐counterfeiting, etc. However, most reported MPCs can only sense stretching or pressure and exhibit poor sensitivity, which greatly limits their applications. Here, sensitive MPCs with brilliant structural colors capable of sensing both stretching and pressures are fabricated by combining self‐assembly and photo‐polymerization processes. The non‐closely packed structures and high reflectance enable MPCs with outstanding mechanochormic performances. The photo‐initiator concentration and thickness have a dramatic influence on the reflectance, wavelength, and even color uniformity. Interestingly, the same MPC shows diverse sensitivity values under stretching or pressing, and the sensitivity of the MPC by pressing is much higher than that by stretching due to their different deformations along three‐dimensional directions. These results are helpful for gaining a deeper understanding of the mechanochromic mechanism and sensitivity. In addition, dynamic patterns with tailorable color contrasts based on pressure and visual sensing based on stretching in practical applications are realized by taking the above advantages of MPCs. This study offers new insight into understanding mechanochromic behavior and will advance their applications in sensing, printing, and information encryption.